KEPENTINGAN INDONESIA MENANDATANGANI NOTA KESEPAHAMAN PENANGGULANGAN PENYALAHGUNAAN NARKOBA DENGAN NIGERIA TAHUN 2013 - Vanesia D. Hutabarat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research explains about Indonesia’s interest in signing the Memorandum of Understanding with Nigeria in 2013 on the cooperation in drug abuse prevention including combating illicit production, manufacture, and trafficking in narcotic drugs, psychotropic substances, and its precursor. Indonesia as a great nation tries to spread its influence in the international system by strengthening its security from the external treats such as drug abuse. As states are security seeking, states tend to replicate each other on the unit level, thus leading to a balancing behavior. The globalization has made everything borderless and instant. As that fact, Indonesia needs to have a good relation with other states to accomplish its goals and interests. In this case, Indonesia decided to do a cooperation with Nigeria which is prone to drug problems but it has achievements in solving that. Indonesia and Nigeria have a good history of relations and both countries also have joined together in the several same international organizations.The perspective of this research is neo-realism. The international system is anarchy and there is no higher authority above the states as the main units, that is why neorealism then talks about the importance of the distribution of power. The distribution of capabilities is largely determined by the number of great powers in the international community. This research uses qualitative methods with techniques of writing a literature review through the secondary data which are already available in the literature and website searches. The collected data are analyzed with theoretical approaches related to International Relations and International Cooperation.The research indicates that Indonesia signed the memorandum of understanding with Nigeria on the drug abuse prevention not only because Nigeria has achievements in solving drug problems but also because Indonesia tries to enter the Nigeria’s domestic market and keep the good relations in many objects.Keywords: Drug Abuse, Indonesia, Interest, Memorandum of Understanding, Nigeria